Tax Administration : Designing a Business Continuity Plan for an Epidemic - Brondolo, John (Technical Notes and Manuals; Technical Notes and Manuals, 2020)
This technical note and manual (TNM) addresses the following questions: What is a business continuity plan (BCP) and what are its main components? What are a BCP's key design considerations for an epidemic? What are the organizational and management arrangements for a BCP? How does a BCP maintain a tax agency's critical functions during an epidemic? and How does a tax agency keep its BCP current and ready for deployment?